2023
DOI: 10.1021/acs.orglett.2c04199
|View full text |Cite
|
Sign up to set email alerts
|

Piperazine Bridged Thianorrole Dimer

Abstract: Oxidative cyclization of open chain thiabilanes yielded the first examples of unique piperazine bridged thianorrole dimers instead of the expected thianorrole monomer. In the thianorrole dimer, the two thianorrole monomeric units are linked via two direct pyrrole C–C bonds by involving the inverted pyrrole and adjacent pyrrole rings of each thianorrole macrocycle and generate a six-membered piperazine ring that bridges the two thianorrole macrocycles. The spectral studies indicated that the thianorrole dimers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The aromatic trithia p ‐benzihexaphyrins 4 – 6 and nonaromatic doubly N‐fused trithia p ‐benzihexaphyrins 7 – 9 were prepared by adopting the 4+2 condensation method as shown in Scheme 1. The appropriate unsymmetrical p ‐benzi thiophene‐based tetrapyrrane precursor 12 was prepared in a sequence of two steps, starting with the previously synthesized (4‐(thiophen‐2‐yl)phenyl)( p ‐tolyl)methanol (mono‐carbinol) 10 by following the reported method [27] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The aromatic trithia p ‐benzihexaphyrins 4 – 6 and nonaromatic doubly N‐fused trithia p ‐benzihexaphyrins 7 – 9 were prepared by adopting the 4+2 condensation method as shown in Scheme 1. The appropriate unsymmetrical p ‐benzi thiophene‐based tetrapyrrane precursor 12 was prepared in a sequence of two steps, starting with the previously synthesized (4‐(thiophen‐2‐yl)phenyl)( p ‐tolyl)methanol (mono‐carbinol) 10 by following the reported method [27] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] The benzene ring can be incorporated in the porphyrinoid macrocyclic framework via 1,3-linking (m-benziporphyrinoids) or 1,4-linking ( p-benziporphyrinoids). [15][16][17] Over the years, studies have revealed that the m-phenylene ring in m-benziporphyrinoids is generally not involved in the π-conjugation with the rest of the macrocyclic conjugation and hinders the π-delocalization in the macrocyclic core; thereby, the macrocycles normally exhibit non-aromatic features. [18][19][20] On the other hand, the p-phenylene ring in p-benziporphyrinoids generally participates in π-delocalization with the rest of the macrocycle and the p-benziporphyrinoids exhibit characteristics ranging from nonaromatic to aromatic, and in some cases, antiaromatic, characteristic features.…”
Section: Introductionmentioning
confidence: 99%